The Image of the Patient as a Component of the World's Image of Students of Medical University - Samoilenko N.V; Dyachenko E.V (Moscow State University of Psychology and Education, 2020)
The article provides data on the study of the patient's image as a component of the image of the world among students of a medical university. The theoretical and methodological foundation was the provision that the image of the patient is implicitly represented in the semantic space of future doctors by semantic categories in the structure of a holistic multi-level system of ideas about the world, other people, about themselves and their activities, i.e. image of the world. The patient's image was studied as a factor in the effectiveness of the interaction between the doctor and the patient in the provision of medical care. The effectiveness of interaction is one of the tools for making relevant clinical decisions, taking into account the opinion of the patient, which ensures patient-oriented medical consultation. 300 students of the 1 and 6 courses of the Ural State Medical University of the Faculty of Medicine were examined. The patient's image was experimentally studied using methods: semantic personality differential, color metaphors and color choices. Based on the results obtained, it is concluded that the image of a patient in medical students is represented by various kinds of semantic categories (friendly, irrational, irritable, etc.). The content of the semantic categories of the patient's image differs at the beginning and at the end of training: from multidirectional characteristics to ordered in the form of a typical and ideal patient. It has been established that the content of the patient's image can be purposefully formed when mastering the educational program. The inclusion of an educational module in clinical teaching disciplines on the skills of professional communication with the patient (as one of the tools for making clinical decisions in the provision of medical care) affects the change in the content of the patient's image in future doctors.